Long-term risk and outcome of infection-related hospitalization in granulomatosis with polyangiitis: a nationwide population-based cohort study. (2nd November 2018) - Faurschou, M; Obel, N; Baslund, B
Abstract : Objective : To assess the long-term risk and outcome of infection-related hospitalization (IH) among patients with granulomatosis with polyangiitis (GPA). Method : We used administrative databases to establish a GPA cohort (n = 398), construct a comparison cohort of population controls (n = 3980), and collect clinical data. Cox regression analyses were used to determine hazard ratios (HRs) as a measure of relative risk. Follow-up began at date of GPA diagnosis and continued for up to 10 years. Results : GPA patients had a markedly increased long-term risk of IH compared to controls [HR (95% confidence interval) year 1: 9.5 (7.0–12.8); years 2–5: 3.2 (2.4–4.3); years 6–10: 2.6 (1.8–3.9)]. Increased long-term risks were found for hospital-treated pneumonia, urinary tract infection, sepsis, and skin infection. We did not observe a lower risk of IH for people diagnosed with GPA during 2005–2014 than for those diagnosed during 1995–2004. Mortality at 3 and 6 months after IH did not differ significantly between patients diagnosed with vasculitis during 2005–2014 and those diagnosed during 1995–2004. Charlson Comorbidity Index score ≥1 was identified as a predictor of pneumonia and urinary tract infection in the GPA cohort, but not of sepsis or skin infection. Conclusion : Patients with GPA have a high risk of IH, even after prolonged follow-up. The long-term risk of IH and mortality after IH did not decline across recent calendar periods among Danish GPA patients. These observations underscore the need for clinical strategies to reduce the burden of infectious complications in GPA.